In the jungle - Greenburg, J. C. (Judith C.); Gerardi, Jan (New York Random House, 2007)
Lost in an Australian rainforest, Andrew, Judy, and Thudd the robot, who are still the size of insects, must evade Rhinoceros beetles, tarantulas, flesh-eating plants, and a host of other threats as they make their way toward the village where Uncle Al will meet them.
"A Stepping Stone book."
Keywords: Rain forests -- Fiction; Robots -- Fiction; Cousins -- Fiction; Australia -- Fiction